Immunization of Male Rabbits with Pseudomonas aeruginosa Increases Spermatogenesis - Areej Abbas Zabbon (World Journal of Experimental Biosciences, 2015)
The impact of immunity on spermatogenesis is documented in the literature. This study highlighted the influence of Pseudomonas aeruginosa hyper-immunization on male rabbit testicular spermatogenesis as the effect of immune response on sex hormones changes. Morphometric criteria were used to evaluate spermatogenesis. The level of hormone was estimated by enzyme-linked immunosorbent assay (ELISA). We found that male rabbits vaccinated with the bacteria showed a highly significant (P
Keywords: Pseudomonas aeruginosa, Sex hormones, Spermatogenesis